Combating heart attacks with knowledge - Nature Research (16552612) (2016)
Approximately 31% of all deaths each year worldwide are due to heart-related diseases, 80% of which are due to heart attacks and strokes. ST elevation myocardial infarction (STEMI) is the most severe form of heart attack. It happens when a blood clot completely occludes one of the main blood vessels feeding the heart, damaging heart muscle and leading to chest pain, difficulty in breathing and profuse sweating. People suffering from this form of heart attack have a better chance of surviving when treated within the first six hours of the onset of symptoms by means of one of a variety of methods used to restore blood flow to the affected heart tissue. Researchers in Saudi Arabia interviewed 79 STEMI patients presenting to King Abdulaziz Cardiac Center in Riyadh between October 2013 and July 2014. They also obtained access to their medical charts. The team found that approximately one-third of the patients they interviewed presented in-hospital more than six hours after the onset of symptoms. Two-thirds of the patients who presented late had a low level of education (primary or below) and a full three-quarters had no previous knowledge of the condition. Late hospital presentation was also significantly higher among those living outside the city. And late presenters had a higher prevalence of other chronic diseases compared to the early presenters, with nearly 80% of the delayed group being diabetics. Longstanding diabetes can lead to the development of nerve dysfunctions that can limit the sensation of chest pain, the researchers explain. Since early treatment is so important, programmes need to be designed to educate the general public but also specifically those most at-risk about the symptoms of heart attacks and what should be done if they arise. “Raising public awareness of the disease and creating programs to educate those at higher risk remains a high priority to ensure the best outcome for these patients,” conclude the researchers in their paper published in the Qatar Medical Journal. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0